Poly-victimization and resilience portfolios: Trends in violence research that can enhance the understanding and prevention of elder abuse. Issue 4 (19th October 2016) - Hamby, Sherry; Smith, Alli; Mitchell, Kimberly; Turner, Heather
ABSTRACT: This literature review assesses the current state of knowledge about elder abuse and mistreatment, focusing on the lack of incorporation of all forms of elder victimization and the benefits of a poly-victimization framework. This review also includes existing knowledge on risk factors and calls for a greater focus on protective factors and a greater inclusion on family and community factors. Future research, prevention, and intervention would benefit from considering the true burden of elder victimization and a greater implementation of strengths-based approaches to programs.